2018
DOI: 10.1186/s40794-018-0072-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and drug susceptibility pattern of Salmonella isolates from apparently healthy slaughter cattle and personnel working at the Jimma municipal abattoir, south-West Ethiopia

Abstract: BackgroundSalmonella species are among the most common food borne pathogens worldwide and their infection is one of the major global public health problems. During the last decade, multidrug resistant Salmonella species have greatly increased in humans and animals. So the aim of this study was to determine prevalence and antibiotic susceptibility pattern of Salmonella in apparently healthy slaughterer cattle and personnel working at the Jimma abattoir.MethodA cross-sectional study was conducted from May to Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 17 publications
3
23
1
Order By: Relevance
“…During this period, 6 full articles and three published abstracts representing 11 datasets were retrieved using the search engines (6775). The majority of these studies were reported from Africa (67, 68, 7074) except for two studies from Europe (69) and South America (75). Among the total of 5,868 cattle examined, 9.2% (554/6018), which is nearly equal to the pooled prevalence estimate, were reported to be positive for Salmonella species with different serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, 6 full articles and three published abstracts representing 11 datasets were retrieved using the search engines (6775). The majority of these studies were reported from Africa (67, 68, 7074) except for two studies from Europe (69) and South America (75). Among the total of 5,868 cattle examined, 9.2% (554/6018), which is nearly equal to the pooled prevalence estimate, were reported to be positive for Salmonella species with different serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1475 Salmonella serovars were isolated from 34 included studies. Of these, 430 were only from animal products [ 22 – 24 , 26 , 32 , 36 , 37 , 40 , 47 , 48 , 53 ], 331 were only from animal specimens [ 25 , 27 , 30 , 43 , 45 , 46 , 51 , 52 ], 249 were from human/animal/animal product [ 28 , 29 , 34 , 35 , 41 , 49 , 54 ] and the rest were from others samples [ 21 , 31 , 33 , 38 , 39 , 42 , 44 , 50 ] as presented on Table 1 . Based on the region, the majority of the isolates (n = 487) were from Oromia region followed by Addis Ababa (n = 369), SNNRP (N = 159) and Amhara (n = 173) [ 26 , 50 , 52 ] ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, seven studies included human, animal, and animal product specimens, three studies included both animal and animal products and the rest three included both human and animal products Table 1. A total of 1475 Salmonella serovars were isolated from 34 included studies. Of these, 430 were only from animal products [22-24, 26, 32, 36, 37, 40, 47, 48, 53], 331 were only from animal specimens [25,27,30,43,45,46,51,52], 249 were from human/animal/animal product [28,29,34,35,41,49,54] and the rest were from others samples [21,31,33,38,39,42,44,50] as presented on Table 1. Based on the region, the majority of the isolates (n = 487) were from Oromia region followed by Addis Ababa (n = 369), SNNRP (N = 159) and Amhara (n = 173) [26,50,52] (Fig 2).…”
Section: Plos Onementioning
confidence: 99%
“…The study showed that the organism is widely prevalent and resistant to most antibiotics. 25 Studies from Ethiopia has shown that the resistance profile is worsening even in domestic animals like dogs. In a study which looked at the presence of Salmonella in digs, it was found that 11.7% were positive for Salmonella.…”
Section: Antimicrobial Resistance Patterns In Animal Health Sector Inmentioning
confidence: 99%
“…Significantly, resistance to three or more antimicrobials was detected in 45% of the isolates. 25 Misuse of antimicrobial agents and non-adherence to standard recommendations on the withdrawal period is a problem across the continent. In a study done in Kenya, it was found that informally marketed cow's milk also had significant presence of antibiotic residues.…”
Section: Antimicrobial Resistance Patterns In Animal Health Sector Inmentioning
confidence: 99%